The Structure of Religious Thought in Ancient Egypt - Dr. Kholoud Habeeb Kareem; Inas. Abbas Jaber AI Saggar (Journal of College of Education, 2025)
This study discusses the early ideas that embodied ancient Egyptian religious thought, beginning with their knowledge of God and their use of various names, including both masculine and feminine. It appears that these ideas originally emphasized the pluralism that characterized religious thought in the ancient world at this stage, before the first humans achieved monotheism. The ancient Egyptians used the word "Neter" to denote the singular form of "god." This word appears in Egyptian texts in the singular form (Ntr) or (Ntr), in the dual form (Ntrwj), the dual feminine form (Ntrtj), and in the masculine plural (Ntrw) and the feminine plural (Ntrwt). This sign is similar in meaning to the Sumerian sign (Denkar) and the sign of El in the Arabian Peninsula. Although all ancient religions were characterized by complexity and ambiguity, Egyptian religion was distinguished by it more than others. This is perhaps due to the abundant diversity in all aspects of civilization and the penetration of religion into various aspects of life. Religion emerged directly from the customs of prehistoric farmers and shepherds. One of the most important features that distinguished Egyptian religious thought from that of other peoples of the ancient Near East was its creativity regarding the afterlife.
Keywords: Ancient Egypt; Talih; Pharaoh; life after death